THE DISTRIBUTION OF BARYON MATTER IN THE NEARBY X-RAY GALAXY CLUSTERS - Babyk, Iu. V.; Vavilova, I. B. (Одеські астрономічні публікації, 2012)
We present the results on the distribution of baryon matter in the galaxy clusters (z < 0.2), based on the Chandra X-ray Observatory data. The observed surface brightness profiles were approximated by β- model, which provides a good fit for all clusters. We found a correlation between cluster’s radius R200 and temperature T , taking into account that their measurements are statistically independent because of the mass of gas is almost independent on cluster’s temperature: R200 = 850 kpc x T 0.61±0.04 keV. We obtained an empirical relation for a total mass of baryon matter (intercluster medium and galaxies), and the upper limit (25-30%) on its changes in a total mass of nearby X-ray galaxy clusters.